Behavioral and neuropathological characterization over the adult lifespan of the human tau knock-in mouse - Benskey, Matthew J.; Panoushek, Spencer; Saito, Takashi; Saido, Takaomi C.; Grabinski, Tessa; Kanaan, Nicholas M. (Frontiers in Aging Neuroscience, 2023)
Tau is a microtubule-associated protein with a diverse functional repertoire linked to neurodegenerative disease. Recently, a human tau knock-in (MAPT KI) mouse was developed that may overcome many limitations associated with current animal models used to study tau. In MAPT KI mice, the entire murine Mapt gene was replaced with the human MAPT gene under control of the endogenous Mapt promoter. This model represents an ideal in vivo platform to study the function and dysfunction of human tau protein. Accordingly, a detailed understanding of the effects MAPT KI has on structure and function of the CNS is warranted. Here, we provide a detailed behavioral and neuropathological assessment of MAPT KI mice. We compared MAPT KI to wild-type (WT) C57BL/6j mice in behavioral assessments of anxiety, attention, working memory, spatial memory, and motor performance from 6-24 months (m) of age. Using immunohistological and biochemical assays, we quantified markers of glia (microglia, astrocytes and oligodendrocytes), synaptic integrity, neuronal integrity and the cytoskeleton. Finally, we quantified levels of total tau, tau isoforms, tau phosphorylation, and tau conformations. MAPT KI mice show normal cognitive and locomotor behavior at all ages, and resilience to mild age-associated locomotor deficits observed in WT mice. Markers of neuronal and synaptic integrity are unchanged in MAPT KI mice with advancing age. Glial markers are largely unchanged in MAPT KI mice, but glial fibrillary acidic protein is increased in the hippocampus of WT and MAPT KI mice at 24m. MAPT KI mice express all 6 human tau isoforms and levels of tau remain stable throughout adulthood. Hippocampal tau in MAPT KI and WT mice is phosphorylated at serine 396/404 (PHF1) and murine tau in WT animals displays more PHF1 phosphorylation at 6 and 12m. Lastly, we extended previous reports showing that MAPT KI mice do not display overt pathology. No evidence of other tau phosphorylation residues (AT8, pS422) or abnormal conformations (TNT2 or TOC1) associated with pathogenic tau was detected. The lack of overt pathological changes in MAPT KI mice make this an ideal platform for future investigations into the function and dysfunction of tau protein in vivo.